2016
DOI: 10.1007/s00586-016-4594-1
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral tubular approach for bilateral laminotomy: effect on ipsilateral and contralateral buttock and leg pain

Abstract: MIS tubular laminotomy through a unilateral approach results in clinically effective bilateral decompression of LSS and lateral recesses, regardless of the approach side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
3
25
0
1
Order By: Relevance
“…Surgical procedures aim to decompress the nerve root emerging from the thecal sac along its course in the lateral recess. A multitude of surgical procedures for surgical decompression of symptomatic lateral recess stenosis have been described ranging from standard open laminectomies to minimally invasive decompressive techniques (14)(15)(16)(17)(18)(19)(20)(21)(22). In the current study we describe the surgical technique of endoscopic interlaminar lateral recess decompression in a small cohort of patients with unilateral symptomatic lateral recess stenosis with well-defined radiographic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical procedures aim to decompress the nerve root emerging from the thecal sac along its course in the lateral recess. A multitude of surgical procedures for surgical decompression of symptomatic lateral recess stenosis have been described ranging from standard open laminectomies to minimally invasive decompressive techniques (14)(15)(16)(17)(18)(19)(20)(21)(22). In the current study we describe the surgical technique of endoscopic interlaminar lateral recess decompression in a small cohort of patients with unilateral symptomatic lateral recess stenosis with well-defined radiographic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…11,30,31 Patients suffering from LCS receive conservative treatment as a primary line of management for symptomatic relief, however; treatment failure or progression of neurological symptoms designate necessity for surgical resolution. 4,50 On a traditional basis, open decompressive laminectomy has been exceedingly utilized in management of LCS refractory to medical treatment with variable success rate ranging between 62-70%. 35,50,54 Nonetheless, post-procedural delayed spinal instability with concomitant rise in fusion procedures attributable to loss of native support taken over by posterior osseoligamentous structures was a major concern.…”
Section: Introductionmentioning
confidence: 99%
“…This technique incorporates a midline incision, opening the fascia, retracting the muscles, hemilaminectomy, bilateral flavectomy, and decompression (5,18). Since BDUA has several advantages such as less blood loss, a shorter stay in hospital, lower complication rates, and less traumatization of surrounding tissues, it has been increasingly applied by neurosurgeons for the treatment of LSS over the past two decades (1,4,13,14,16,19,22). However, this technique has some disadvantages such as accidental dural tears, root…”
Section: █ Discussionmentioning
confidence: 99%
“…Machado et al reviewed different surgical methods for decompression and widening the spinal canal in LSS and reported that decompression plus fusion, or expanding the interspinous process spaces was not superior to conventional decompression alone (12,17). Many current articles have suggested the avoidance of bilateral laminectomy and instrumentation because bilateral decompression with a unilateral approach (BDUA) has been shown to be effective in reducing pain, increasing walking distance, and improving disability (1,13,14,16,19,22). However, some reports have demonstrated that although unilateral laminectomy is effective in the early postoperative period, it has poor outcomes in the long term (approximately 5 years) (6,10).…”
Section: █ Introductionmentioning
confidence: 99%